Environmental issues as a non-financial reporting area using the example of selected companies listed on the Warsaw Stock Exchange - Czaja-Cieszyńska, Hanna (Kwestie środowiskowe jako obszar raportowania niefinansowego na przykładzie wybranych spółek notowanych na Giełdzie Papierów Wartościowych w Warszawie, 2020)
The purpose of this article is to assess the comparability of non-financial disclosures on the impact of economic activity on the natural environment in reports of selected companies listed on the Warsaw Stock Exchange. The ten largest listed companies listed in the WIG-20 index were selected for the study. The analysis of the reports was based on the following disclosure categories: Materials and raw materials, Fuels and energy, Water, Biodiversity, Emissions to the atmosphere, Waste and Effluents, and Others. Within these categories, 14 key environmental non-financial indicators were defined. The empirical study carried out confirmed that the non-financial reports analyzed in all of the seven categories of disclosures were not fully comparable. The research methods used were: literature studies, analysis of legal regulations, analysis of secondary data, as well as methods of induction and synthesis.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 9, s. 45-56
Keywords: non-financial reports; natural environment; GRI Standards; non-financial information standard; CRS